A Bibliometrics-Based Review of Domestic Research in the Field of Artificial Intelligence - Wang, Chong; Chen, Zixi (International Journal of Computer Science and Information Technology, 2024)
Artificial Intelligence (AI) is a technology that simulates human intelligence and has been rapidly developed in recent years. With the continuous development of the Internet and big data technology, AI technology has been widely applied and studied. In this paper, using "artificial intelligence" as the keyword, we searched the core journals on China Knowledge Network, selected 8913 effective documents from 2015-2023 as the research samples, and used the scientific bibliometric methods such as word frequency analysis, cluster analysis, and theme evolution analysis, and visualized and analyzed them with the help of COOC software, to synthesize the research hotspots in the field of artificial intelligence. The hotspots, development and evolution history of research in the field of artificial intelligence are sorted out, and the future research direction and application prospects are prospected.